2015
DOI: 10.1002/2015gl064182
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear subcyclotron resonance as a formationmechanism for gaps in banded chorus

Abstract: An interesting characteristic of magnetospheric chorus is the presence of a frequency gap at ω≃0.5Ωe, where Ωe is the electron cyclotron angular frequency. Recent chorus observations sometimes show additional gaps near 0.3Ωe and 0.6Ωe. Here we present a novel nonlinear mechanism for the formation of these gaps using Hamiltonian theory and test particle simulations in a homogeneous, magnetized, collisionless plasma. We find that an oblique whistler wave with frequency at a fraction of the electron cyclotron fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…For the linear Landau damping mechanism, ray tracing studies show that waves at 0.5f ce suffer significant damping only after they have propagated a significant distance from the equatorial region (see, e.g., Bortnik et al, 2006). Similar argument could be made about the subcyclotron resonance mechanism proposed by Fu et al (2015). The nonlinear damping mechanism by Omura et al (2009) cannot be applied to explain this study, because the damping rate of this mechanism and its dependence on plasma parameters are not given.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…For the linear Landau damping mechanism, ray tracing studies show that waves at 0.5f ce suffer significant damping only after they have propagated a significant distance from the equatorial region (see, e.g., Bortnik et al, 2006). Similar argument could be made about the subcyclotron resonance mechanism proposed by Fu et al (2015). The nonlinear damping mechanism by Omura et al (2009) cannot be applied to explain this study, because the damping rate of this mechanism and its dependence on plasma parameters are not given.…”
Section: Discussionmentioning
confidence: 68%
“…Tsurutani and Smith (1974) suggested that Landau damping by electrons with energy of cyclotron resonance but traveling at the same direction as the wave might be responsible for the power gap. Fu et al (2015) suggested that the subcyclotron resonance between large amplitude whistler waves and energetic electrons may be responsible of the multiple power gaps of chorus reported by Macúšová et al (2014). Fu et al (2015) suggested that the subcyclotron resonance between large amplitude whistler waves and energetic electrons may be responsible of the multiple power gaps of chorus reported by Macúšová et al (2014).…”
Section: Introductionmentioning
confidence: 97%
“…The evidences of this nonlinear damping mechanism have been observed by Geotail satellite in Yagitani et al (). Fu et al () performed subcyclotron resonance, which might lead to the formation of the gap by test particle simulations in a homogeneous background magnetic field. However, the gradient of the background magnetic field is essential for nonlinear wave‐particle interactions (Omura et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The lower band ( ∕Ω e < 0.5, is the wave frequency) is dominantly parallel propagating with some portion close to the resonance cone [Agapitov et al, 2013;Li et al, 2013], whereas the upper band ( ∕Ω e > 0.5) has a broad range of wave normal angles between 0 ∘ and 60 ∘ [Li et al, 2013]. Several mechanisms have been proposed to account for the banded structure of chorus [Omura et al, 2009;Liu et al, 2011;Fu et al, 2014;Mourenas et al, 2015;Fu et al, 2015]. Among the proposed mechanisms, Mourenas et al [2015] suggested that the less frequently occurring but statistically significant very oblique lower band chorus waves can be generated through a combination of cyclotron resonance and Landau resonance with low-energy electron beams having an energy of a few keV.…”
Section: Introductionmentioning
confidence: 99%